Digital employee experience and performance: The mediating role of wellbeing and engagement - Awaldi, Awaldi; Raharjo, Kusdi; Noerman, Teuku; Ruhana, Ika (Edelweiss Applied Science and Technology, 2026)
This study explores the strategic role of Digital Employee Experience (DEX) in influencing employee well-being, engagement, and performance within the context of digital transformation in the airline industry. Grounded in Social Cognitive Theory (SCT) and the Job Demands–Resources (JD–R) Model, it integrates cognitive and motivational perspectives to explain how digital work environments affect employees’ psychological and behavioral outcomes. Using a quantitative explanatory design, data were collected from 312 employees of Garuda Indonesia through an online survey and analyzed with Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results indicate that DEX significantly enhances wellbeing (β = 0.688; p<0.001) and engagement (β = 0.412; p<0.001). Wellbeing positively influences engagement (β = 0.482; p < 0.001), while engagement strongly improves performance (β = 0.569; p<0.001). A sequential mediation effect was confirmed, showing that well-being and engagement jointly mediate the relationship between DEX and performance (β = 0.310; p<0.001). Theoretically, this study extends SCT and JD–R by positioning digital experiences as cognitive mechanisms and motivational job resources. Practically, the findings emphasize that employee-centered digital ecosystems promote well-being, engagement, and sustainable performance, highlighting that successful digital transformation must balance technological advancement with human empowerment.